2021
DOI: 10.1108/mrr-03-2021-0238
|View full text |Cite
|
Sign up to set email alerts
|

The effects of organizational justice, trust and supervisor–subordinate guanxi on organizational citizenship behavior: a social-exchange perspective

Abstract: Purpose This study aims to use a social exchange perspective to investigate the influence of organizational justice on organizational citizenship behavior (OCB). Design/methodology/approach Survey and interview data were collected from a sample of insurance firm sales representatives in Taiwan. Structural equation modeling was deployed to explore the relationship between organizational justice, trust, supervisor–subordinate guanxi and OCB. Findings The findings offer important theoretical, managerial and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 67 publications
0
4
0
1
Order By: Relevance
“…Several studies (Ertürk, 2007;Yardan et al, 2014;Erkutlu, 2011;Kwon Choi et al, 2014;Yu, 2022) confirmed the positive relationship between organizational justice and OCB of employees working in different industries. Yardan et al (2014) found a significant relationship between each dimension of organizational justice and civic virtue and conscientiousness behaviors of nurses, midwives, laboratory technicians, and medical secretaries at a hospital.…”
Section: The Effect Of Interactional Justice On Ocbmentioning
confidence: 91%
See 2 more Smart Citations
“…Several studies (Ertürk, 2007;Yardan et al, 2014;Erkutlu, 2011;Kwon Choi et al, 2014;Yu, 2022) confirmed the positive relationship between organizational justice and OCB of employees working in different industries. Yardan et al (2014) found a significant relationship between each dimension of organizational justice and civic virtue and conscientiousness behaviors of nurses, midwives, laboratory technicians, and medical secretaries at a hospital.…”
Section: The Effect Of Interactional Justice On Ocbmentioning
confidence: 91%
“…Kwon Choi et al (2014) indicated that the effects of interactional justice on the OCB of employees in Korea were mediated by organizational identification. Yu (2022) found that trust and supervisor-subordinate guanxi mediate the relationship between organizational justice and OCB of firm sales representatives in Taiwan. Taken together, the following hypotheses are proposed: H1: Interactional Justice positively relates to the OCB of employees.…”
Section: The Effect Of Interactional Justice On Ocbmentioning
confidence: 92%
See 1 more Smart Citation
“…The Chinese term guanxi , which implies informal personal contacts and is seen as an implicit psychological contract between individuals, has been increasingly getting attention from scholars (Chen and Chen, 2004). Some studies have confirmed the relationship between supervisor-subordinate guanxi in promoting extra-role behaviors at organizations (Liu and Wang, 2013; Yu, 2022) but the ethical side of guanxi which is built on trust and positive emotion of employee remain controversial among scholars (Leung and Wong, 2001). Utilizing principles from social learning theory, this study posits that ethical leaders within the public sector function as a favorable model for employees to emulate with respect to ethical standards.…”
Section: Introductionmentioning
confidence: 99%
“…Yazar anahtar kelimelerine göre yapılan ortak kelime analizi sonucunda, Sosyal Mübale Kuramı ile birlikte en sık kullanılan kelimenin "güven" olduğu sonucuna ulaşılmıştır. Gerçekten de sosyal mübadelenin önemli bir bileşeni olan güven, tekrarlanan mübadele ilişkilerinde kuramın ortaya çıkacağını öngördüğü bir sonucu ve aynı zamanda bu sosyal mübadele ilişkisinin kalitesini etkileyen en önemli faktörüdür(Ertürk ve Vurgun, 2015; Lioukas ve Reuer, 2015: Yu, 2022. Dolayısıyla araştırmacıların bu nedenlerle, çalışmalarında her iki konuyu sıklıkla birlikte ele aldıkları düşünülebilir.…”
unclassified